ANALISIS PUISI “KEMARAU” KARYA IKA MUSTIKA DENGAN MENGGUNAKAN PENDEKATAN MIMETIK - Siti Nurlaela Sabiah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Poetry is an imaginative literary work that serves as an entertaining reading. However, not a few poems are difficult to know the meaning or meaning, due to a lack of knowledge in analyzing the meaning of the poem. Therefore, understanding is needed in analyzing a poem with various approaches. The aim of this research is to find out the meaning of Ika Mustika poem entitled "Kemarau", and to increase understanding of the mimetic approach. The mimetic approach is a literary work that connects life's conflicts with imitation of nature. Ika Mustika poetry is formed from a unique language structure and has a broad meaning that makes readers interested in his work. This research is very useful for readers and writers in producing a literary work in the form of poetry. The method used in this research is descriptive qualitative method, namely by presenting the results of the study in the form of words. The author got this source from the book “Mustika 40 Puisi”. The results of this poetry analysis explain the mood in terms of waiting, this poem looks simple but has a very broad meaning. The author analogizes the meaning of poetry into an expression that not everyone understands.